Respuesta :

Answer:

[tex]f(x) = 6x^2 - 11x + 4[/tex]

[tex]g(x) = 3x - 4[/tex]

[tex]q(x) = 2x - 1[/tex]

Step-by-step explanation:

Represent the two polynomials with [tex]f(x)[/tex] and [tex]g(x)[/tex]

Let

[tex]f(x) = 6x^2 - 11x + 4[/tex]

[tex]g(x) = 3x - 4[/tex]

The quotient of two polynomial is the result of division between the two polynomials

Let q(x) represent the quotient polynomial

[tex]q(x) = \frac{f(x)}{g(x)}[/tex]

Where g(x) is the divisor

[tex]q(x) = \frac{6x^2 - 11x + 4}{3x - 4}[/tex]

Factorize the numerator

[tex]q(x) = \frac{6x^2 - 3x - 8x + 4}{3x - 4}[/tex]

[tex]q(x) = \frac{(3x -4)(2x - 1)}{3x - 4}[/tex]

[tex]q(x) = 2x - 1[/tex]

Notice that: q(x) and g(x) have the same degree of 1